2020
DOI: 10.1371/journal.pone.0233958
|View full text |Cite
|
Sign up to set email alerts
|

The shape of the transverse arch in high heels while standing

Abstract: Introduction High heeled shoes have long been worn in society and they are known to cause biomechanical imbalances to not only the foot, but the whole musculoskeletal system. This study aims to show the detailed changes that happen to the shape of the transverse arch of the foot in high heels, using two different inclination degrees. Methods 68 women participated in this study. Two custom-made high heels were made with inclinations of 15 degrees and 30 degrees (cm). A weight-bearing ultrasound was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The corset, which caused Victorian women to faint from restricted airflow (Boston Globe, 1893), has made a recent comeback for women (Bateman, 2020), along with other restrictive clothing and shapewear meant to slim, while defining and enhancing curves. Wearing high‐heeled shoes similarly is associated with long term damage to the feet (e.g., Zeidan et al., 2020), in addition to pain. Recently, tattooed makeup (another painful procedure) has become a popular aesthetic practice, despite risks of infection and lesions (U.S. Food & Drug Administration, 2020; Vagefi et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The corset, which caused Victorian women to faint from restricted airflow (Boston Globe, 1893), has made a recent comeback for women (Bateman, 2020), along with other restrictive clothing and shapewear meant to slim, while defining and enhancing curves. Wearing high‐heeled shoes similarly is associated with long term damage to the feet (e.g., Zeidan et al., 2020), in addition to pain. Recently, tattooed makeup (another painful procedure) has become a popular aesthetic practice, despite risks of infection and lesions (U.S. Food & Drug Administration, 2020; Vagefi et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…25.9% (n=99) of participants aged 26-30 years. 16 Table-4 is categorized according to the cross-tabulation between pain and shoe heel height, 199 of the women affected with moderate pain who had worn heels greater than one inch, 50 women had mild pain, and 47 women had severe pain due to heel height of their shoe more than one inch. Fifty-six women had experienced moderate pain, 17 women had mild pain, and 13 women had pain due to shoe heel height less than or equal to one inch.…”
Section: Resultsmentioning
confidence: 99%
“…Foot pain is widespread nowadays in our society, and the leading factors are shoe heel height and an individual's weight. A study conducted in 2020 by Zeidan concluded that wearing high-heeled shoes leads to increased pressure on the metatarsal head and causes pressure on various tissues of the foot 16 . Similarly, the result of this study also shows that wearing high heels caused foot pain among working females and the majority of women in this study pointed to heels as the most common site of pain.…”
Section: Discussionmentioning
confidence: 99%
“…27 All measurements were performed in both unloaded and loaded positions at 50% of the subject's weight. 28…”
Section: Windlass Testmentioning
confidence: 99%